2019
DOI: 10.1093/mnras/stz3193
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian fluid approach for the modeling of peculiarities of the interstellar dust distribution in the astrospheres/heliosphere

Abstract: Interstellar dust penetrates into the heliosphere/astrosphere due to relative motion of the Sun and the local interstellar medium (LISM). Inside the heliosphere/astrosphere and at the heliospheric boundaries, where the solar/stellar wind interacts with LISM, distribution of the interstellar dust is modified due to an action of electromagnetic forces, the solar gravitation and radiation pressure. In this paper we show that the distribution of the interstellar dust particles in the heliosphere has peculiarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In this paper we demonstrated that the singularities of the ISD density in the heliosphere, discovered using the Lagrangian approach in Mishchenko et al (2020), can also be found by the Monte-Carlo simulations. This requires super-small computational cells.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In this paper we demonstrated that the singularities of the ISD density in the heliosphere, discovered using the Lagrangian approach in Mishchenko et al (2020), can also be found by the Monte-Carlo simulations. This requires super-small computational cells.…”
Section: Discussionmentioning
confidence: 74%
“…It was shown by Mishchenko et al (2020) that in the case of zero dispersion the ISD trajectories form caustics at which the number density of ISD is infinite. A caustic is an envelope of the ISD trajectories.…”
Section: Singularities In Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…(4), the FLA is still approximately 20 times more efficient than box-counting methods for twodimensional simulations [4,10]. Another analysis found that a box-counting approach for number density requires ∼ 10 6 trajectories to be computed, whereas the FLA only needs ∼ 10 3 trajectories to obtain the same level of detail, however this is offset by the additional expense of calculating the Jacobian along trajectories which entails a fortyfold increase in computational cost for three-dimensional simulations, and also by linear interpolation of the trajectory number density data onto the Eulerian grid which takes almost as long as the numerical integration along trajectories [14]. Therefore, despite providing a 10 3 saving on the number of trajectories computed when compared against the box-counting approach, the overall efficiency improvement of the FLA for calculation of the Eulerian number density field is reduced to around tenfold.…”
Section: Computational Advantagementioning
confidence: 99%
“…Previous works have addressed this by using the fact that the sign of the Jacobian determinant J changes every time a droplet crosses the trajectory of another droplet, effectively providing a means of keeping track of which layer of the droplet field a given trajectory is in. Since each layer of the droplet field is single-valued with non-intersecting trajectories, interpolation can be used to calculate the Eulerian number density within each individual layer, and then due to the number density field being additive the contributions from each layer at a given point are summed together to obtain the total number density [11,14,17]. This requires that droplets are indexed in such a way that a distinction is made every time a fold is crossed, with the most straightforward means of doing this being to keep count of the number of times this occurs for each droplet, then all droplets with the same count index form one layer of the droplet field [17].…”
Section: Numerical Considerationsmentioning
confidence: 99%